Seven Deadly Sins of Manuscript Writing: Reflections of Two Experienced Reviewers. Issue 3 (1st October 2016) - Trail, Galen T.; James, Jeffrey D.
ABSTRACT: Acceptance rates of quality journals in the sport management field are typically below 20%. We have identified seven problems that often prevent submitted manuscripts from being accepted: (1) Failure to derive research from theory and/or a failure to consider more than one potential theory to support the research. (2) No synthesis of existing, similar information already published within the sport field. (3) A lack of assessment of the validity of prior research. (4) Creation of new scales when existing scales work sufficiently well. (5) Limiting potential explanatory variance. (6) Not reporting the variance explained and/or a failure to discuss the meaningfulness of the results. (7) A lack of reporting viable alternative explanations when the data do not support the hypotheses or focal model. We discuss each of these issues and provide examples, both good and bad.